The Symbolic White Supremacy Towards Native American in Avatar (2009) Movie - Wa Ode Ariyanti; Ansor Putra (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2017)
This research investigated the Avatar movie by James Cameron to show the symbolicexpressions of white supremacy towards Native Americans. The opposition resulted in a crisis of hegemony and in the end, the class subordinate resisted, this is what Gramsci meant as the War of Position. This movie shows that supremacy in the way of hegemony is more successful to the way of domination, but the hegemony and dominance were not successful when the allies carried out the opposition.